Fluid flow measurement / Nor Liawati Abu Othman, Rosita Priman and Marliza Abdul Jalal - Abu Othman, Nor Liawati; Priman, Rosita; Abdul Jalal, Marliza (Faculty of Mechanical Engineering, 2001)
Measurement of fluid flow is not only necessary in the research laboratories but is used in almost all types of industries. The need of measuring fluid flow measurement, ranges from biological applications such as measurements of blood flow rate in the human artery to highly advance application such as measurement of the flow of liquid oxygen in a rocket. Fluid flow measurement techniques and devices can be very simple and cheap or be very sophisticated and technologically advanced, which only specialized research centers would be able to own. The purpose of this project is for the students to gain as much theoretical knowledge and practical experiences on fluid flow measurements devices and technique as possible, particularly those which are widely used in industries and laboratories. In order to achieve the above objectives, the following course of actions were formulated.